Signature of the Paleo-Course Changes in the São Francisco River as Source of Genetic Structure in Neotropical Pithecopus nordestinus (Phyllomedusinae, Anura) Treefrog - Bruschi, Daniel Pacheco; Peres, Elen Arroyo; Lourenço, Luciana Bolsoni; Bartoleti, Luiz Filipe de Macedo; Sobral-Souza, Thadeu; Recco-Pimentel, Shirlei Maria (Frontiers in Genetics, 2019)
Historical processes that have interrupted gene flow between distinct evolutionary lineages have played a fundamental role in the evolution of the enormous diversity of species found in the Neotropical region. Numerous studies have discussed the role of geographic barriers and Pleistocene forest refugia in the diversification of the region’s biodiversity. In the present study, we investigated the relative contribution of these different factors to the evolutionary history of Pithecopus nordestinus, a Neotropical tree-frog, which is amply distributed in the Brazilian Atlantic Forest and adjacent areas of the Caatinga biome. We used an extensive sample and multilocus DNA sequences to provide an overview of the intraspecific genetic diversity of P. nordestinus, characterize historical diversification patterns, and identify possible phylogenetic splits. We tested different scenarios of diversification based on Pleistocene Refugia and river barrier models using Approximate Bayesian Computation (ABC) and Ecological Niche Modeling (ENM). The phylogenetic approach indicate the occurrence of processes of phylogeographic divergence in both time and space, related to historical shifts in the course of the São Francisco River during Plio-Pleistocene period, resulting in two principal, highly divergent clades. The ABC model provided strong statistical support for this scenario, confirming the hypothesis that the São Francisco River acted as an effective geographical barrier during vicariant events in the evolutionary history of P. nordestinus. We believe that the climatic changes that occurred during the Pleistocene also played a secondary role in the genetic signatures identified, reinforcing the divergence of populations isolated by physical barriers. These findings reinforce the conclusion that the two models of diversification (geographic barriers and refugia) are not mutually exclusive in the Neotropical domain, but may interact extensively during the diversification of species on a regional scale.